Teorija elit i elitarnyj sport v rossijskom obscestve - Kosheleva, A. V. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The becoming and development of market relations in Russia have affected all sides of public life. The sharp stratification of the society has caused interest to studying elite. Nowadays its researches can be divided into three directions. The first one is focused on revealing the place of elite in the social structure and on the analysis of its structure. The second one is focused on studying the influence of elite on the transformation of the society. The third one - on inspection of the certain groups of elites, such as political, regional, financial. However the sports elite, elite sports are not investigated in any of the directions and groups though nowadays their influence on the society is serious and great enough.